A comparative study on different physicochemical properties of fresh and frozen lamb meat (Journal of the Bangladesh Agricultural University, 2017)
This study described the comparison of different physicochemical parameters between fresh and frozen lamb meat. The pH measurement for fresh and frozen lamb meat did not show a significant difference. CIE L*a*b* (Commission Internationale de l'éclairage) color measurement technique was used and ∆E (distance between 2 colors) was found 5.32. On shrinkage measurement, there were significant differences (p